CASE REPORT The role of CRRT in optimizing management of septic shock in patient with miastenia gravis improve outcome - amin, robby al; irawany, vera (JAI (Jurnal Anestesiologi Indonesia), 2021)
Septic shock is a medical emergency characterized by organ dysfunction due to the body's uncontrolled response to infection, with a high mortality rate. The combination of Myasthenia Gravis (MG), pneumonia, and septic shock requires prompt and appropriate management to prevent further complications and improve patient prognosis. In this case, a 47-year-old female patient with Myasthenia Gravis developed septic shock due to pneumonia and showed significant clinical improvement after hemodynamic stabilization, appropriate antibiotic therapy, and the use of Continuous Renal Replacement Therapy (CRRT) to regulate electrolyte balance and eliminate inflammatory mediators. Despite the absence of plasmapheresis, comprehensive management of sepsis and organ dysfunction successfully improved the patient's prognosis. Optimal sepsis therapy and the use of CRRT without plasmapheresis may serve as an alternative approach in managing MG patients with septic shock due to pneumonia. Stabilizing the patient's condition through infection control, organ support, and comprehensive MG therapy plays a crucial role in successful treatment. Further research is needed to evaluate teh effectiveness of this approach in a broader patient population